The Handbook of Pluralistic Counselling and Psychotherapy - Edited by Cooper, Mick and Dryden, Windy (Los Angeles SAGE, 2016)
'An excellent volume that will be of interest to all therapists (from trainee to more experienced practitioner) who have any curiosity about pluralistic therapy.' - Andy Pendle, Senior Lecturer in Counselling, Coaching and Mentoring, York St John University
Include Index
Keywords: Psychotherapy -- Counseling psychology -- Counseling